PENGELOLAAN PEMBELAJARAN IPS DENGAN PENDEKATAN CONTEXTUAL TEACHING AND LEARNING (CTL) DI SEKOLAH STANDAR NASIONAL (Studi Situs SMP Negeri 1 Grobogan, Kabupaten Grobogan) - Mulyanto, Tri (2011)
Research purposes are: (1) describing classroom layout character in SMP Negeri 1 Grobogan Grobogan subdistrict. (2) describing character of contextual teaching and learning social knowledge material in SMP Negeri 1 Grobogan Grobogan subdistrict. (3) describing contextual teaching and learning social knowledge learning interaction character in SMP Negeri 1 Grobogan Grobogan subdistrict. Kind of this research is qualitative research. Research location is in SMP Negeri 1 Grobogan, Grobogan subdistrcit. Collecting data techniques are participated observation, interview and documentation. Data analysis technique in this research uses descriptive technique with three procedures, they are: (1) data reduction, (2) data presentation, and (3) conclusion or verification. Research results: (1) classroom layout managed clasically, for special learning mode teacher changes classroom layout into U mode, conference mode, and group mode, it depends on teacher need. Classroom layout arrangement execution submit to school guide. (2) contextual social knowledge learning material management in SMP Negeri 1 Grobogan, includes three activities are: planning, teaching and learning process, and learning evaluation. RPP/ lesson plan of contextual learning in SMP Negeri 1 Grobogan is curriculum establishment and sylabus made by class teacher according to exist curriculum and syllabus. (3) children social interaction in contextual social learning lesson is very communicative, in contextual learning student tends to do two ways communication, it is done friendly and casually, each students help each other. Interaction in contextual social knowledge learning execution is educative interaction in mutual relation between teacher (educator) and student, in a teaching system. Educative interaction is the most important factor to get well learning and teaching situation.